Análise funcional de comportamentos estereotipados em indivíduos com deficiência visual - Baston, Camila Aparecida Paris (Universidade Federal de São Carlos, 2019)
The present study aimed to analyze stereotyped behaviors in individuals with visual impairment (blindness or low vision), since individuals with this diagnosis may also present these stereotyped behaviors. The theoretical foundation of this research is based on descriptive functional analysis through a registration protocol filled in multiprofessional appointments in a Clinical Hospital in the Subnormal Vision sector and in a Special Institution for the visually impaired. The implementation of this research, with the discussions of functional analysis, was given from the perspective of behavior analysis theorists. This study is descriptive and quantitative in nature. Stereotyped behaviors of six four-to-17-year-old participants with low vision or blindness were recorded. For each target behavior, antecedent events and consequences were recorded in a specific protocol. The results indicated that the stereotypes had the function of obtaining attention or escaping from demands. It is discussed, mainly, if the descriptive functional analysis is sufficient for the identification of these functions and it compares the results found with data of the literature of the area of visual deficiency.
Functional analysis of stereotypeed behavior in individuals with visual deficiency
Keywords: Educação especial; Deficiência visual; Análise do comportamento; Análise funcional descritiva; Estereotipias; Special education; Visual deficiency; Behavior analysis; Descriptive functional analysis; Stereotypies; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO